The Relationship of Family Support With Mother's Motivation in Exclusive Breast Milk in 1-6 Months Old Babies During Pandemic Covid 19 in Sidotopo Wetan Surabaya - Novita Anggraini; Fatimawati, Iis; Merina Widyastuti; Lela Nurlela (Kirana Publisher (KNPub), 2023)
Mother's motivation is very decisive in exclusive breastfeeding for 6 months. A mother who has good motivation will continue to try to breastfeed her baby. The purpose of this study was to analyze the relationship between family support and mother's motivation in exclusive breastfeeding for infants aged 1-6 months in Sidotopo Wetan Village, Surabaya. Analytical research design with a cross sectional approach with a research sample of 80 nursing mothers respondents in Sidotopo Wetan Surabaya Village were selected using quota sampling. The instrument used is a questionnaire on family support and mother's motivation. Data analysis using Spearman Rho test. The results showed that family support for breastfeeding mothers in Sidotopo Wetan Surabaya, resulted in 51 people (63.8%) being categorized as low, while the motivation of mothers in breastfeeding in Sidotopo Wetan showed that 55 people (68.8%) had moderate motivation. It can be concluded that there is a relationship between family support and mother's motivation in exclusive breastfeeding for infants aged 1-6 months during the pandemic in Sidotopo Wetan Village, Surabaya. (p = 0.001) Support from other people or those closest to them plays a very important role in the success or failure of exclusive breastfeeding. With high family support, it affects the mother's motivation in exclusive breastfeeding for infants aged 1-6 months. With the implication of health workers to provide education that support from the family is very important in exclusive breastfeeding